THE EFFECTIVENESS OF RECIPROCAL TEACHING LEARNING MODEL TOWARD RESULT OF MATHEMATICS LEARNING OUTCOMES IN STUDENTS CLASS VII OF SMP NEGERI 2 SLEMAN - Erni Andriyani; Uswatun Khasanah (Universitas Ahmad Dahlan, 2017)
The dominant model of learning that teachers lead students more passive in participating in learning activities, especially mathematics. So, that students become less familiar with the material describe teachers. This affects the result of students in mathematics learning. This study aims to determine the effectiveness of the Reciprocal Teaching-learning model toward the result of mathematics learning outcomes in students class VII. The population in this study is the seventh-grade students of SMP Negeri 2 Sleman in the academic year 2015/2016 which consists of 5 classes. The sampling technique using a purposive sampling technique and obtained class VII C as an experimental class and class VII B as a control class. The data was collected using documentation and the test method. The data analysis technique used analysis prerequisites of normality test, homogeneity test, and hypothesis testing. The result showed that (1) there is a different learning outcomes between learning mathematics using learning model Reciprocal Teaching with learning mathematics using learning model Ekspositori. It’s based on two hypothesis test obtained and with significance level of 5% and the degrees of freedom, respectivelyand , which meanings , and than is rejected and accepted. (2) Learning mathematics using learning model Reciprocal Teaching is more effective than learning mathematics using learning model Ekspositori through mathematics learning outcomes on seventh-grade students of SMP Negeri 2 Sleman in the academic year of 2015/2016. It is based on the one hypothesis test obtained dan with significance level of 5% and the degrees of freedom, respectively and which means , and than is rejected and accepted.